Krishna
0

Step 1: Before going to do the problem, Find the known and unknowns in and note it down.


Step 2: Explore the given rule

          EXAMPLE: x_{n+1} = ax_n - 3

          Succeeding term = a (preceding term) - 3


Step 3: By using the given rule find the required term ( x_2, x_3,x_4...etc)

            [NOTE: To find the twenty-first term, replace n(any variable represents  

            position) by 21. based up on the rule it(n) may change to lower value or

          higher value]

            

EXAMPLE: For an attempt to find the x_3

x_{n+1} = ax_n - 3

x_3 = ax_2 - 3

Substitute the values x_2(calculate\ it\ or\ given\ in\ the\ question\ x_2=a-3)

x_ 3 = a(a - 3) - 3

x_3 = a^2 - 3a - 3


Step 4: Simplify further


Step 5: Verify that the result and the given answer are same or not